Negative photosensitive resin composition, negative photosensitive resin composition film, cured film, and electronic component

JP7643503B2Active Publication Date: 2025-03-11TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023180755
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-24
Filing Date
2023-10-20
Publication Date
2025-03-11
Estimated Expiration
2040-08-27

AI Technical Summary

Benefits of technology

【0009】 本発明の樹脂脂組成物は、パターン加工性を有し、低温硬化条件において硬化膜のガラス転移温度と硬化膜の引張強度·引張伸度に優れた樹脂組成物、組成物フィルム、硬化膜、これらを用いた中空構造体および、半導体装置を提供するものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643503000001
    Figure 0007643503000001
  • Figure 0007643503000002
    Figure 0007643503000002
  • Figure 0007643503000003
    Figure 0007643503000003
Patent Text Reader

Abstract

To provide a resin composition and a resin composition film which are excellent in pattern processing properties and film strength, and a semiconductor device using them.SOLUTION: A resin composition contains (A) a polymer compound, (B) a cation-polymerizable compound and (C) a cation polymerization initiator, wherein (A) the polymer compound has a carboxylic acid residue as its molecular chain terminal.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a resin composition film, a cured film, a hollow structure using these, and a semiconductor device. More specifically, the present invention relates to a resin composition suitable for use in a surface protection film, an interlayer insulating film, a structure of a MEMS (microelectromechanical systems), etc., of a semiconductor element or an inductor device. [Background technology]

[0002] Conventionally, polyimide-based materials and polybenzoxazole-based materials, which have excellent heat resistance, electrical insulation properties, and mechanical properties, have been widely used for surface protection films and interlayer insulating films of semiconductor elements. In recent years, with the demand for higher density and performance of semiconductor elements, photosensitive materials are required for surface protection films and interlayer insulating films from the viewpoint of production efficiency.

[0003] On the other hand, photosensitive materials are required to be processed to have high aspect ratios for various packaging structures of recent semiconductor elements and MEMS. In order to meet such demands, chemically amplified photocationic polymerization photosensitive materials have been disclosed (for example, Patent Document 1). In addition, photocationic polymerization materials intended to improve mechanical and thermal properties by incorporating epoxy resins of specific structures in chemically amplified photocationic polymerization systems have been disclosed (for example, Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2008 / 007764 Brochure [Patent Document 2] JP 2019-38964 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, it is difficult for the photo-cationic polymerization material to have sufficient mechanical properties and thermal properties at the same time. Specifically, when the crosslink density is increased in order to improve the glass transition temperature of the cured film, which is an index of thermal properties, the tensile strength and tensile elongation of the cured film, which are indexes of mechanical properties, are deteriorated. On the other hand, when a softening component is introduced in order to improve the tensile strength and tensile elongation, the glass transition temperature of the cured film is decreased.

[0006] In view of this situation, the authors conducted extensive research and discovered that a photocationic polymerization material using at least one polymer compound selected from the group consisting of polyamide, polyimide, polyamideimide, and polybenzoxazole has pattern processability and provides a cured film with excellent glass transition temperature and tensile strength / tensile elongation. [Means for solving the problem]

[0007] The present invention for solving the above problems is as follows.

[0008] A negative-type photosensitive resin composition that contains (A) a polymer compound and (B) a cationic polymerizable compound and is cured by a cationic polymerization reaction, The polymer compound (A) , Po At least one compound selected from the group consisting of polyimide and polyamideimide, the (A) polymer compound has a structure derived from an alicyclic tetracarboxylic dianhydride, the (A) polymer compound has a molecular chain terminal structure derived from a carboxylic acid residue, The resin composition further comprises (C) a cationic polymerization initiator. Effect of the Invention

[0009] The resin composition of the present invention provides a resin composition, a composition film, and a cured film which have pattern processability and which exhibit excellent glass transition temperature and excellent tensile strength and tensile elongation under low-temperature curing conditions, as well as hollow structures and semiconductor devices each using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The resin composition of the present invention is a resin composition containing (A) a polymer compound and (B) a cationically polymerizable compound, wherein the (A) polymer compound is at least one compound selected from the group consisting of polyamide, polyimide, polyamideimide, and polybenzoxazole, and further contains (C) a cationic polymerization initiator.

[0011] As described later, the polymer compound (A) is at least one compound selected from the group consisting of polyamide, polyimide, polyamideimide, and polybenzoxazole. The polyimide precursor and the polybenzoxazole precursor correspond to the above-mentioned polyamide, respectively.

[0012] The resin composition of the present invention, containing the polymer compound (A), has excellent film-forming properties when formed into a film, and the cured film has excellent tensile strength and tensile elongation. The weight-average molecular weight of the polymer compound (A) is not particularly limited, but is preferably 1,000 or more and 200,000 or less. The polymer compound (A) may be used alone or in combination of two or more kinds. The weight-average molecular weight of the polymer compound (A) in the present invention is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0013] The resin composition of the present invention preferably contains a polymeric compound (A) whose molecular chain terminal is a carboxylic acid residue. More specifically, the resin composition of the present invention contains a polymeric compound (A), and the molecular chain terminal of the polymeric compound (A) is preferably a structure derived from a carboxylic acid residue. The resin composition of the present invention can contain a polymeric compound whose molecular chain terminal is not a structure derived from a carboxylic acid residue, as long as it contains a polymeric compound (A) whose molecular chain terminal is a structure derived from a carboxylic acid residue. In addition, when the resin composition of the present invention contains a polymeric compound whose molecular chain terminal is not a structure derived from a carboxylic acid residue, the content is preferably as low as possible. Specifically, the content of the polymeric compound whose molecular chain terminal is not a structure derived from a carboxylic acid residue is preferably 0 parts by mass or more and 10 parts by mass or less, more preferably 0 parts by mass or more and 5 parts by mass or less, and particularly preferably 0 parts by mass or more and 2 parts by mass or less, relative to a total of 100 parts by mass of the polymeric compounds (A) whose molecular chain terminal is a structure derived from a carboxylic acid residue.

[0014] The resin composition of the present invention preferably contains a polymeric compound (A) whose molecular chain terminal is derived from a carboxylic acid residue, and the content is not particularly limited as long as the polymeric compound (A) whose molecular chain terminal is derived from a carboxylic acid residue is contained, but the content is preferably 20% by mass to 95% by mass, more preferably 30% by mass to 85% by mass, and particularly preferably 30% by mass to 70% by mass in 100% by mass of the resin composition. By containing 20% ​​by mass or more of the polymeric compound (A) whose molecular chain terminal is derived from a carboxylic acid residue in the resin composition, the film strength of the cured film is improved. On the other hand, by making the content of the polymeric compound (A) whose molecular chain terminal is derived from a carboxylic acid residue 95% by mass or less in the resin composition, the cationic polymerization reaction is easily progressed, and the chemical resistance of the cured film is improved. Furthermore, more preferably, the content of the polymeric compound (A) whose molecular chain terminal is derived from a carboxylic acid residue in the resin composition is 70% by mass or less.

[0015] The (A) polymer compound preferably has a structure in which the molecular chain terminal is derived from a carboxylic acid residue. By having the (A) polymer compound have a structure in which the molecular chain terminal is derived from a carboxylic acid residue, the molecular chain terminal can have a molecular structure that does not have an amine terminal structure that can be an inhibitory functional group for cationic polymerization, and as a result, even when polyamide, polyimide, or polyamideimide is used, sufficient cationic polymerizability can be exhibited, which is preferable.

[0016] Here, the structure derived from a carboxylic acid residue at the molecular chain terminal of the (A) polymer compound is an organic group derived from a carboxylic acid residue that can constitute a polyamide, polyimide, or polyamideimide, and refers to a structure derived from a monocarboxylic acid, dicarboxylic acid, monoacid chloride compound, diacid chloride compound, tetracarboxylic acid, acid anhydride, acid dianhydride, etc. Among the above, it is particularly preferable that the structure derived from a carboxylic acid residue at the molecular chain terminal of the (A) polymer compound is a structure derived from a tetracarboxylic acid dianhydride. The structure derived from a tetracarboxylic acid dianhydride at the molecular chain terminal is preferable in terms of improving the storage stability of the resin composition before heat curing. On the other hand, it is preferable in terms of improving the heat resistance and chemical resistance after heat curing, since the terminal carboxylic acid anhydride group becomes a reactive functional group as a cured film.

[0017] Furthermore, the polymer compound (A) is preferably alkali-soluble. If it is alkali-soluble, it is preferable because it can be developed with an aqueous alkali solution without using an organic solvent that is a factor of environmental load during development during pattern processing. The term "alkali-soluble" as used herein refers to a compound that dissolves at 0.1 g or more at 25° C. in 100 g of a 2.38 mass % aqueous solution of tetramethylammonium hydroxide. In order to express alkali solubility, it is desirable for the polymer compound (A) to have an alkali-soluble functional group. The alkali-soluble functional group is a functional group having acidity, and specific examples thereof include a phenolic hydroxyl group, a carboxyl group, and a sulfonic acid group. Among the above-mentioned alkali-soluble functional groups, the alkali-soluble functional group is preferably a phenolic hydroxyl group in view of problems such as storage stability of the photosensitive resin composition and corrosion of copper wiring, which is a conductor. In other words, the polymer compound (A) is preferably a compound having a phenolic hydroxyl group in the molecular chain.

[0018] (A) Examples of the structure (organic group) in which the molecular chain terminal of the polymer compound is derived from a carboxylic acid residue include, but are not limited to, aromatic dicarboxylic acids, aromatic acid dianhydrides, alicyclic dicarboxylic acids, alicyclic acid dianhydrides, aliphatic dicarboxylic acids, aliphatic acid dianhydrides, etc. These may be used alone or in combination of two or more.

[0019] Among these, an organic group derived from an alicyclic carboxylic acid residue is preferred, since it is possible to design a resin that is transparent to the wavelength used during patterning, and as a result, it is possible to achieve fine pattern processability in a thick film.

[0020] In the present invention, the (A) polymeric compound is preferably the polyamide, polyimide, or polyamideimide, and is preferably a compound having at least one structure selected from the structures represented by general formula (1) and general formula (2).

[0021] [ka]

[0022] (In the general formulas (1) and (2), X 1 and X 2 each independently represents a divalent to decavalent organic group; Y 1 and Y 2 each independently represents a divalent to tetravalent organic group, R represents a hydrogen atom or an organic group having 1 to 20 carbon atoms, q represents an integer of 0 to 2, and r, s, t, and u each independently represents an integer of 0 to 4. Y in formulas (1) and (2) 1 and Y 2 represents a divalent to tetravalent organic group, and represents an organic group derived from a diamine.

[0023] Y in the general formulas (1) and (2) of the polymer compound (A) 1 and Y 2 It is preferable that the diamine residue having a phenolic hydroxyl group is contained in the resin. By containing the diamine residue having a phenolic hydroxyl group, appropriate solubility of the resin in an alkaline developer can be obtained, so that a high contrast between exposed and unexposed areas can be obtained and a desired pattern can be formed.

[0024] Specific examples of diamines having a phenolic hydroxyl group include aromatic diamines such as bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl)ether, bis(3-amino-4-hydroxy)biphenyl, 2,2'-ditrifluoromethyl-5,5'-dihydroxyl-4,4'-diaminobiphenyl, bis(3-amino-4-hydroxyphenyl)fluorene, and 2,2'-bis(trifluoromethyl)-5,5'-dihydroxybenzidine; compounds in which a portion of the hydrogen atoms of these aromatic rings or hydrocarbons is substituted with an alkyl group or fluoroalkyl group having 1 to 10 carbon atoms, a halogen atom, or the like; and diamines having the structure shown below, but are not limited thereto. The other diamines to be copolymerized can be used as they are, or as the corresponding diisocyanate compounds or trimethylsilylated diamines. Two or more of these diamine components can also be used in combination.

[0025] [ka]

[0026] [ka]

[0027] Y in formulas (1) and (2) 1 and Y 2may contain a diamine residue having an aromatic group other than those mentioned above. By copolymerizing these, the heat resistance can be improved. Specific examples of the diamine residue having an aromatic group include 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl methane, 4,4'-diaminodiphenyl methane, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 1,4-bis(4-aminophenoxy)benzene, benzine, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4- ... Examples of the aromatic diamines include aromatic diamines such as 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl, and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, and compounds in which a part of the hydrogen atoms of these aromatic rings or hydrocarbons is substituted with an alkyl group or fluoroalkyl group having 1 to 10 carbon atoms, a halogen atom, or the like, but are not limited thereto. The other diamines to be copolymerized can be used as they are or as the corresponding diisocyanate compounds or trimethylsilylated diamines. Two or more of these diamine components may be used in combination.

[0028] In the present invention, in the above general formula (1) and general formula (2), X 1 and X 2 represents a carboxylic acid residue, which is a divalent to decavalent organic group.

[0029] The carboxylic acid residue preferably has a structure derived from an alicyclic tetracarboxylic dianhydride. In other words, the (A) polymer compound is at least one compound selected from the group consisting of polyamide, polyimide, and polyamideimide, and further preferably has a structure derived from an alicyclic tetracarboxylic dianhydride. When the carboxylic acid residue has a structure derived from an alicyclic tetracarboxylic dianhydride, the light transmittance of the resin composition at the exposure wavelength is increased, and processing in a thick film of 20 μm or more is facilitated. Furthermore, although the reason is unclear, the (A) polymer compound has a structure derived from an alicyclic tetracarboxylic dianhydride, which is preferable in that the reactivity of cationic polymerization is higher than that of aromatic acid dianhydrides, and the chemical resistance of the cured film is improved.

[0030] Furthermore, among the alicyclic tetracarboxylic acid dianhydrides, alicyclic tetracarboxylic acid dianhydrides having a polycyclic structure are preferred because they improve the chemical resistance and ion migration resistance of the cured product.

[0031] Moreover, the polymer compound (A) of the present invention preferably has a structure derived from a compound represented by at least one of the following general formulas (3) and (4).

[0032] [ka]

[0033] (In the formula, R 1 , R 2 , R 3 each independently represents a hydrogen atom or a methyl group. The (A) polymer compound has a structure derived from the compound represented by general formula (3) or (4), and the resin skeleton has flexibility, which is preferable in that the resin composition before curing has high solubility in organic solvents, is less likely to cause resin precipitation in the composition, and has excellent storage stability.

[0034] Specific examples of the organic group derived from an alicyclic tetracarboxylic dianhydride having a polycyclic structure include 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)-4-methyl-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride, 4-(2,5-dioxotetrahydro furan-3-yl)-7-methyl-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride, norbornane-2-spiro-2'-cyclopentanone-5'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride, and norbornane-2-spiro-2'-cyclohexanone-6'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride.

[0035] The carboxylic acid residue may include an acid dianhydride other than the alicyclic tetracarboxylic dianhydride having a polycyclic structure. Specifically, pyromellitic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 2,3,3',4'-biphenyl tetracarboxylic dianhydride, 2,2',3,3'-biphenyl tetracarboxylic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, Dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl) Aromatic tetracarboxylic dianhydrides such as fluorene dianhydride, 9,9-bis{4-(3,4-dicarboxyphenoxy)phenyl}fluorene dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 2,3,5,6-pyridine tetracarboxylic dianhydride, 3,4,9,10-perylene tetracarboxylic dianhydride, and 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 1 Examples of the dianhydride include, but are not limited to, 2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, 2,3,5-tricarboxy-2-cyclopentane acetic dianhydride, 2,3,4,5-tetrahydrofuran tetracarboxylic dianhydride, etc. These may be used alone or in combination of two or more.

[0036] The molar ratio of the structures represented by general formulas (1) and (2) in the present invention can be confirmed by a method of calculation from the molar ratio of monomers used in polymerization, or a method of detecting peaks of a polyamide structure, an imide precursor structure, or an imide structure in the obtained resin, resin composition, or cured film using a nuclear magnetic resonance (NMR) device.

[0037] The (A) polymeric compound having a structure derived from a carboxylic acid residue at the molecular chain end can be obtained by increasing the content of acid anhydride relative to the diamine used in polymerization, for example, in the case of a polyimide having a carboxylic acid residue at the molecular chain end. In this case, when the total of the carboxylic acid residues in the (A) polymeric compound is taken as 100 mol%, the total of the amine residues is preferably 60 mol% or more and 98 mol% or less. In other words, the (A) polymeric compound is preferably a compound obtained by polymerizing the total of the amine residues to 60 to 98 mol% when the total of the carboxylic acid residues is taken as 100 mol%. When the total of the amine residues is 60 mol% or more, the weight average molecular weight is likely to be 1,000 or more, and the film-forming property is excellent when made into a film, and when it is 98 mol% or less, the proportion of the polymeric compound having an amine residue at the end is small, the cationic polymerization reaction is likely to proceed, and the chemical resistance of the cured film is improved.

[0038] As another method for obtaining the (A) polymeric compound having a structure in which the molecular chain terminal is derived from a carboxylic acid residue, it is also possible to obtain the compound by using a specific compound, specifically, an acid anhydride, a monocarboxylic acid, a monoacid chloride compound, or a monoactive ester compound, from among the compounds generally used as an end-capping agent.

[0039] In addition, by capping the molecular chain ends of the (A) polymer compound with a terminal capping agent of a carboxylic acid or acid anhydride having a hydroxyl group, a carboxyl group, a sulfonic acid group, a thiol group, a vinyl group, an ethynyl group, or an allyl group, the dissolution rate of the (A) polymer compound in an alkaline aqueous solution and the mechanical properties of the resulting cured film can be easily adjusted to preferred ranges. In addition, multiple terminal capping agents may be reacted to introduce multiple different terminal groups.

[0040] Examples of acid anhydrides, monocarboxylic acids, monoacid chloride compounds, and monoactive ester compounds as end-capping agents include acid anhydrides such as phthalic anhydride, maleic anhydride, nadic anhydride, cyclohexanedicarboxylic anhydride, and 3-hydroxyphthalic anhydride, 3-carboxyphenol, 4-carboxyphenol, 3-carboxythiophenol, 4-carboxythiophenol, 1-hydroxy-7-carboxynaphthalene, 1-hydroxy-6-carboxynaphthalene, 1-hydroxy-5-carboxynaphthalene, 1-mercapto-7-carboxynaphthalene, 1-mercapto-6-carboxynaphthalene, 1-mercapto-5-carboxynaphthalene, 3-carboxy Preferred are monocarboxylic acids such as benzenesulfonic acid and 4-carboxybenzenesulfonic acid, monoacid chloride compounds in which the carboxyl groups of these are acid chlorides, monoacid chloride compounds in which only one carboxyl group of dicarboxylic acids such as terephthalic acid, phthalic acid, maleic acid, cyclohexanedicarboxylic acid, 1,5-dicarboxynaphthalene, 1,6-dicarboxynaphthalene, 1,7-dicarboxynaphthalene, and 2,6-dicarboxynaphthalene is acid chloride, and active ester compounds obtained by reacting a monoacid chloride compound with N-hydroxybenzotriazole, imidazole, or N-hydroxy-5-norbornene-2,3-dicarboximide. Two or more of these may be used.

[0041] The polymeric compounds into which these terminal blocking agents have been introduced become polymeric compounds (A) whose molecular chain terminals are derived from carboxylic acid residues. The terminal blocking agents that can be used to obtain polymeric compounds (A) whose molecular chain terminals are derived from carboxylic acid residues can be easily detected by the following method. For example, the polymeric compounds (A) into which terminal blocking agents have been introduced are dissolved in an acidic solution, decomposed into the structural units of amine components and acid anhydride components, and the terminal blocking agents used in the present invention can be easily detected by gas chromatography (GC) or NMR. Apart from this, the resin components into which terminal blocking agents have been introduced can also be easily detected by directly measuring the resin components by pyrolysis gas chromatography (PGC), infrared spectroscopy, and 13C-NMR spectroscopy.

[0042] In the present invention, the (A) polymer compound is synthesized, for example, by the following method, but is not limited thereto. The polyimide structure is synthesized by a known method by replacing a part of the diamine with a primary monoamine as an end-capping agent, or by replacing the tetracarboxylic dianhydride with a dicarboxylic anhydride as an end-capping agent. For example, a polyimide precursor is obtained by using a method such as a method of reacting a tetracarboxylic dianhydride with a diamine compound and a monoamine at low temperature, a method of reacting a tetracarboxylic dianhydride with a dicarboxylic anhydride and a diamine compound at low temperature, or a method of obtaining a diester from a tetracarboxylic dianhydride and an alcohol, and then reacting the diamine with the monoamine in the presence of a condensing agent. Then, a polyimide can be synthesized by using a known imidization reaction method.

[0043] In the present invention, after the polymer compound (A) is polymerized by the above method, it is preferable to put it into a large amount of water or a mixture of methanol and water, precipitate it, filter, dry, and isolate it. The drying temperature is preferably 40 to 100° C., and more preferably 50 to 80° C. This operation removes unreacted monomers and oligomer components such as dimers and trimers, and can improve the film properties after thermal curing.

[0044] In the present invention, the imidization rate can be easily determined, for example, by the following method. First, the infrared absorption spectrum of the polymer is measured, and the absorption peak (1780 cm) of the imide structure due to the polyimide is detected. -1 Near, 1377cm -1 Next, the polymer was heat-treated at 350°C for 1 hour to obtain a sample with a 100% imidization rate, and the infrared absorption spectrum was measured to confirm the presence of the 1377cm -1 By comparing the peak intensities around the imidization rate, the content of imide groups in the resin before heat treatment is calculated, and the imidization rate is determined. Since this suppresses the change in the ring closure rate during heat curing and provides the effect of reducing stress, an imidization rate of 50% or more is preferable, and 80% or more is even more preferable.

[0045] The resin composition of the present invention contains (B) a cationically polymerizable compound. Examples of the (B) cationically polymerizable compound include cyclic ether compounds (epoxy compounds, oxetane compounds, etc.), ethylenically unsaturated compounds (vinyl ethers, styrenes, etc.), bicycloorthoesters, spiroorthocarbonates, and spiroorthoesters.

[0046] As the epoxy compound, known compounds can be used, including aromatic epoxy compounds, alicyclic epoxy compounds and aliphatic epoxy compounds.

[0047] Examples of aromatic epoxy compounds include glycidyl ethers of mono- or polyhydric phenols having at least one aromatic ring (phenol, bisphenol A, phenol novolak, and alkylene oxide adducts thereof).

[0048] Examples of alicyclic epoxy compounds include compounds obtained by epoxidizing a compound having at least one cyclohexene or cyclopentene ring with an oxidizing agent (e.g., 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate).

[0049] Examples of the aliphatic epoxy compounds include polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts (1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, etc.), polyglycidyl esters of aliphatic polybasic acids (diglycidyl tetrahydrophthalate, etc.), and epoxidized products of long-chain unsaturated compounds (epoxidized soybean oil, epoxidized polybutadiene, etc.).

[0050] As the oxetane compound, known compounds can be used, for example, 3-ethyl-3-hydroxymethyl Examples of the aryl oxetane include ethyl oxetane, 2-ethylhexyl (3-ethyl-3-oxetanylmethyl) ether, 2-hydroxyethyl (3-ethyl-3-oxetanylmethyl) ether, 2-hydroxypropyl (3-ethyl-3-oxetanylmethyl) ether, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, oxetanyl silsesquioxetane, and phenol novolac oxetane.

[0051] As the ethylenically unsaturated compound, known cationically polymerizable monomers and the like can be used, including aliphatic monovinyl ethers, aromatic monovinyl ethers, polyfunctional vinyl ethers, styrene and cationically polymerizable nitrogen-containing monomers.

[0052] Examples of the aliphatic monovinyl ether include methyl vinyl ether, ethyl vinyl ether, butyl vinyl ether, and cyclohexyl vinyl ether.

[0053] Examples of the aromatic monovinyl ether include 2-phenoxyethyl vinyl ether, phenyl vinyl ether, and p-methoxyphenyl vinyl ether.

[0054] Examples of polyfunctional vinyl ethers include butanediol-1,4-divinyl ether and triethylene glycol divinyl ether.

[0055] Examples of styrenes include styrene, α-methylstyrene, p-methoxystyrene, and p-butoxystyrene.

[0056] Examples of the cationically polymerizable nitrogen-containing monomer include N-vinylcarbazole and N-vinylpyrrolidone.

[0057] Bicyclo orthoesters include 1-phenyl-4-ethyl-2,6,7-trioxabicyclo[2.2.2]octane and 1-ethyl-4-hydroxymethyl-2,6,7-trioxabicyclo-[2.2.2]octane.

[0058] Examples of spiro orthocarbonates include 1,5,7,11-tetraoxaspiro[5.5]undecane and 3,9-dibenzyl-1,5,7,11-tetraoxaspiro[5.5]undecane.

[0059] Spiro orthoesters include 1,4,6-trioxaspiro[4.4]nonane, 2-methyl-1,4,6-trioxaspiro[4.4]nonane, and 1,4,6-trioxaspiro[4.5]decane.

[0060] Among these cationic polymerizable compounds, epoxy compounds, oxetane compounds and vinyl ethers are preferred, more preferably epoxy compounds and oxetane compounds, and particularly preferably epoxy compounds. Among them, it is preferred to use a polyfunctional epoxy compound that is liquid at room temperature (20°C) and has an epoxy equivalent of 80 g / eq. or more and 160 g / eq. or less. The polyfunctional epoxy compound being liquid at room temperature is preferred in that it improves compatibility with the (A) polymer compound and provides fine pattern processability. On the other hand, it is preferred that the epoxy equivalent of the polyfunctional epoxy compound is 80 g / eq. or more and 160 g / eq. or less, in that it improves the heat resistance and chemical resistance of the cured film.

[0061] Examples of polyfunctional epoxy compounds that are liquid at room temperature and have an epoxy equivalent of 80 g / eq. or more and 160 g / eq. or less include TEPIC-VL (trade name, manufactured by Nissan Chemical Industries, Ltd.), bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, Showfree BATG, and Showfree PETG (trade names, all manufactured by Showa Denko K.K.).

[0062] The (B) cationically polymerizable compound may be used alone or in combination of two or more kinds.

[0063] The content of the (B) cationically polymerizable compound is preferably 30 parts by mass or more, more preferably 50 parts by mass or more, when the total amount of the (A) polymer compounds is taken as 100 parts by mass, in order to exhibit sufficient cationic curability and improve pattern processability, while it is preferably 200 parts by mass or less in order to eliminate tack on the film surface and facilitate handling when made into a film.

[0064] The resin composition of the present invention contains a cationic polymerization initiator (C). The cationic polymerization initiator (C) generates an acid directly or indirectly by light or heat to cause cationic polymerization. As the cationic polymerization initiator (C), any known compound can be used without particular limitation, but a sulfonium salt is preferable. Specific examples of the cationic polymerization initiator (C) include aromatic iodonium complex salts and aromatic sulfonium complex salts. Specific examples of aromatic iodonium complex salts include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, and di(4-nonylphenyl)iodonium hexafluorophosphate. These cationic polymerization initiators (C) may be used alone or in combination of two or more.

[0065] In the present invention, the (C) cationic polymerization initiator is preferably a photo-cationic polymerization initiator. By selecting a photo-cationic polymerization initiator as the (C) cationic polymerization initiator, a contrast in the progress of cationic polymerization can be created between the light-irradiated area and the light-unirradiated area, and a pattern can be formed by dissolving the resin composition in any developer, which is preferable.

[0066] The content of the (C) cationic polymerization initiator is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.7 parts by mass or more, when the (B) cationic polymerizable compound is 100 parts by mass. This allows the cationic polymerizable compound to exhibit sufficient curability and improve pattern processability. On the other hand, in order to improve the storage stability before curing of the resin composition, the content is preferably 10 parts by weight or less, more preferably 8 parts by weight or less.

[0067] The resin composition of the present invention may use a sensitizer to absorb ultraviolet light and provide the absorbed light energy to the photoacid generator. As the sensitizer, for example, an anthracene compound having alkoxy groups at the 9th and 10th positions (9,10-dialkoxy-anthracene derivative) is preferable. Examples of the alkoxy group include C1-C4 alkoxy groups such as methoxy, ethoxy, and propoxy. The 9,10-dialkoxy-anthracene derivative may further have a substituent. Examples of the substituent include halogen atoms such as fluorine, chlorine, bromine, and iodine atoms, C1-C4 alkyl groups such as methyl, ethyl, and propyl groups, sulfonic acid alkyl ester groups, and carboxylic acid alkyl ester groups. Examples of the alkyl in the sulfonic acid alkyl ester group and carboxylic acid alkyl ester group include C1-C4 alkyl groups such as methyl, ethyl, and propyl. The substitution position of these substituents is preferably the 2-position.

[0068] The resin composition of the present invention may contain a thermal crosslinking agent, and a compound having an alkoxymethyl group or a methylol group is preferred.

[0069] Examples of compounds having an alkoxymethyl group or a methylol group include DML-PC, DML-PEP, DML-OC, DML-OEP, DML-34X, DML-PTBP, DML-PCHP, DML-OCHP, DML-PFP, DML-PSBP, DML-POP, DML-MBOC, DML-MBPC, DML-MTrisPC, DML-BisOC-Z, DML-BisOCHP-Z, DML-BPC, DML-BisOC-P, DMOM-PC, DMOM-PTBP, DMOM -MBPC, TriML-P, TriML-35XL, TML-HQ, TML-BP, TML-pp-BPF, TML-BPE, TML-BPA, TML-BPAF, TML-BPAP, TMOM-BP, TMOM-BPE, TMOM-BPA, TMOM-BPAF, TMOM-BPAP, HML-TPPHBA, HML-TPHAP, HMOM-TPPHBA, HMOM-TPHAP (all trade names, manufactured by Honshu Chemical Industry Co., Ltd.), NIKALAC (registered trademark) MX-290, NIKALAC MX-280, NIKALAC MW-100LM, NIKALAC MX-750LM (all trade names, manufactured by Sanwa Chemical Co., Ltd.).

[0070] The resin composition of the present invention may further contain a silane compound. By containing a silane compound, the adhesion of the heat-resistant resin film is improved. Specific examples of the silane compound include N-phenylaminoethyl trimethoxysilane, N-phenylaminoethyl triethoxysilane, N-phenylaminopropyl trimethoxysilane, N-phenylaminopropyl triethoxysilane, N-phenylaminobutyl trimethoxysilane, N-phenylaminobutyl triethoxysilane, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl trichlorosilane, vinyl tris(β-methoxyethoxy)silane, 3-methacryloxypropyl trimethoxysilane, 3-acryloxypropyl trimethoxysilane, p-styryl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, and 3-methacryloxypropyl methyl diethoxysilane.

[0071] Furthermore, the resin composition of the present invention may contain, as necessary, a surfactant for the purpose of improving wettability with a substrate, an ester such as ethyl lactate or propylene glycol monomethyl ether acetate, an alcohol such as ethanol, a ketone such as cyclohexanone or methyl isobutyl ketone, or an ether such as tetrahydrofuran or dioxane, etc. Furthermore, for the purpose of suppressing the thermal expansion coefficient or increasing or decreasing the dielectric constant, the resin composition may contain inorganic particles such as silicon dioxide or titanium dioxide, or polyimide powder, etc.

[0072] The resin composition of the present invention is not limited in shape before curing, and may be in the form of a varnish or a film. The resin composition film of the present invention is a film of the resin composition of the present invention, that is, a resin composition film having a resin composition coating formed from the resin composition of the present invention. Therefore, the resin composition film of the present invention may be a film formed on a support, that is, a resin composition film having a resin composition coating formed from the resin composition of the present invention on a support, or may be in an embodiment without a support. When used in the form of a varnish, a solution of the components (A) to (C) and a component added as necessary in an organic solvent can be used. The resin composition film can be obtained, for example, by applying the resin composition of the present invention to a support and then drying it as necessary.

[0073] Next, a method for producing a resin composition film using the resin composition of the present invention will be described. The resin composition film of the present invention is obtained by applying a solution (varnish) of the resin composition onto a support, and then drying it as necessary. The resin composition varnish is obtained by adding an organic solvent to the resin composition. The organic solvent used here may be any solvent that dissolves the resin composition.

[0074] Specific examples of the organic solvent include ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether; acetates such as ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propyl acetate, butyl acetate, isobutyl acetate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, methyl lactate, ethyl lactate, and butyl lactate; Examples of suitable solvents include ketones such as acetone, methyl ethyl ketone, acetylacetone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, cyclopentanone, and 2-heptanone; alcohols such as butyl alcohol, isobutyl alcohol, pentanol, 4-methyl-2-pentanol, 3-methyl-2-butanol, 3-methyl-3-methoxybutanol, and diacetone alcohol; aromatic hydrocarbons such as toluene and xylene; and others such as N-methyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and γ-butyrolactone.

[0075] The resin composition varnish may be filtered using filter paper or a filter. Although the filtration method is not particularly limited, a method of filtering by pressure filtration using a filter having a retention particle size of 0.4 μm to 10 μm is preferred.

[0076] The resin composition film of the present invention is preferably formed on a support and used. The support is not particularly limited, but various commercially available films such as polyethylene terephthalate (PET) film, polyphenylene sulfide film, polyimide film, etc. can be used. The bonding surface between the support and the resin composition film may be subjected to a surface treatment with silicone, a silane coupling agent, an aluminum chelating agent, polyurea, etc., in order to improve adhesion and peelability. The thickness of the support is not particularly limited, but is preferably in the range of 10 to 100 μm from the viewpoint of workability.

[0077] In addition, the resin composition film of the present invention may have a protective film on the film in order to protect the surface. This can protect the surface of the photosensitive resin composition film from contaminants such as dust and dirt in the atmosphere. Examples of the protective film include polyolefin films and polyester films. It is preferable that the protective film has a small adhesive force with the resin composition film.

[0078] Methods for applying the resin composition varnish to a support include spin coating using a spinner, spray coating, roll coating, screen printing, blade coater, die coater, calendar coater, meniscus coater, bar coater, roll coater, comma roll coater, gravure coater, screen coater, slit die coater, etc. The coating thickness varies depending on the coating technique, the solids concentration of the composition, the viscosity, etc., but it is usually preferable that the coating thickness after drying is 0.5 μm or more and 100 μm or less.

[0079] For drying, an oven, a hot plate, infrared rays, etc. can be used. The drying temperature and drying time may be within a range that allows the organic solvent to volatilize, and it is preferable to appropriately set a range in which the photosensitive resin composition film is in an uncured or semi-cured state. Specifically, it is preferable to perform drying at a range of 40°C to 120°C for 1 minute to several tens of minutes. In addition, the temperature may be increased stepwise by combining these temperatures, and for example, heat treatment may be performed at 70°C, 80°C, and 90°C for 1 minute each.

[0080] Next, a method for patterning the resin composition varnish of the present invention or a resin composition film using the same, and a method for thermocompression bonding to other members will be described with examples.

[0081] First, a method for forming a resin composition film on a substrate using the resin composition of the present invention or a resin composition film using the same will be described. When a resin composition varnish is used, the varnish is first applied onto the substrate. Examples of the application method include spin coating using a spinner, spray coating, roll coating, and screen printing. The coating thickness varies depending on the application method, the solid content concentration and viscosity of the resin composition, and generally, it is preferable to apply the coating so that the film thickness after drying is 0.5 μm or more and 100 μm or less. Next, the substrate coated with the resin composition varnish is dried to obtain a resin composition film. For drying, an oven, a hot plate, infrared rays, etc. can be used. The drying temperature and drying time may be within a range that allows the organic solvent to volatilize, and it is preferable to appropriately set a range in which the resin composition film is in an uncured or semi-cured state. Specifically, it is preferable to perform the drying at a temperature in the range of 50 to 150° C. for 1 minute to several hours.

[0082] On the other hand, when a resin composition film is used, if a protective film is present, it is peeled off, the resin composition film is placed opposite the substrate, and the resin composition film and the substrate are laminated by thermocompression to obtain a resin composition coating. Thermocompression can be performed by heat pressing, heat lamination, heat vacuum lamination, etc. The lamination temperature is preferably 40°C or higher in terms of adhesion to the substrate and embeddability. In addition, in order to prevent the resin composition film from curing during lamination, which deteriorates the resolution of the pattern formation in the exposure and development process, the lamination temperature is preferably 150°C or lower.

[0083] In either case, the substrates used include, but are not limited to, silicon wafers, ceramics, gallium arsenide, organic circuit boards, inorganic circuit boards, and circuit constituent materials arranged on these substrates. Examples of organic circuit boards include glass-based copper-clad laminates such as glass cloth-epoxy copper-clad laminates, composite copper-clad laminates such as glass nonwoven cloth-epoxy copper-clad laminates, heat-resistant thermoplastic substrates such as polyetherimide resin substrates, polyetherketone resin substrates, and polysulfone resin substrates, and flexible substrates such as polyester copper-clad film substrates and polyimide copper-clad film substrates. Examples of inorganic circuit boards include ceramic substrates such as alumina substrates, aluminum nitride substrates, and silicon carbide substrates, and metal substrates such as aluminum-based substrates and iron-based substrates. Examples of circuit constituent materials include conductors containing metals such as silver, gold, and copper, resistors containing inorganic oxides, low dielectrics containing glass-based materials and / or resins, high dielectrics containing resins and high-dielectric-constant inorganic particles, and insulators containing glass-based materials.

[0084] Next, the resin composition film formed by the above method is exposed to actinic rays through a mask having a desired pattern. Actinic rays used for exposure include ultraviolet rays, visible rays, electron beams, X-rays, etc., but in the present invention, it is preferable to use i-rays (365 nm), h-rays (405 nm), and g-rays (436 nm) from a mercury lamp. In the resin composition film, when the support is made of a material transparent to these rays, exposure may be performed without peeling the support from the resin composition film.

[0085] To form a pattern, the exposed portion is removed with a developer after exposure. The developer is preferably an aqueous solution of a compound exhibiting alkalinity, such as an aqueous solution of tetramethylammonium hydroxide, diethanolamine, diethylaminoethanol, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, methylamine, dimethylamine, dimethylaminoethyl acetate, dimethylaminoethanol, dimethylaminoethyl methacrylate, cyclohexylamine, ethylenediamine, or hexamethylenediamine. In some cases, these alkaline aqueous solutions may contain polar solvents, such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, γ-butyrolactone, or dimethylacrylamide, alcohols, such as methanol, ethanol, or isopropanol, esters, such as ethyl lactate or propylene glycol monomethyl ether acetate, or ketones, such as cyclopentanone, cyclohexanone, isobutyl ketone, or methyl isobutyl ketone, either alone or in combination.

[0086] The development can be carried out by spraying the developer on the coating surface, piling the developer on the coating surface, immersing the coating surface in the developer, or immersing the coating surface in the developer and applying ultrasonic waves, etc. The development conditions, such as the development time and the temperature of the developer in the development step, may be any conditions that allow the exposed portion to be removed and a pattern to be formed.

[0087] After development, it is preferable to carry out a rinsing treatment with water. Here, too, the rinsing treatment may be carried out by adding alcohols such as ethanol and isopropyl alcohol, or esters such as ethyl lactate and propylene glycol monomethyl ether acetate to water.

[0088] If necessary, a baking treatment may be performed before development. This may improve the resolution of the pattern after development and increase the allowable range of development conditions. The baking temperature is preferably in the range of 50 to 180°C, more preferably in the range of 60 to 120°C. The time is preferably from 5 seconds to several hours.

[0089] After the pattern is formed, unreacted cationic polymerizable compounds and cationic polymerization initiators remain in the resin composition film. Therefore, they may be thermally decomposed during thermocompression bonding or curing to generate gas. In order to avoid this, it is preferable to irradiate the entire surface of the resin composition film after the pattern is formed with the above-mentioned exposure light to generate acid from the cationic polymerization initiator. By doing so, the reaction of the unreacted cationic polymerizable compounds proceeds during thermocompression bonding or curing, and the generation of gas derived from thermal decomposition can be suppressed.

[0090] After development, a temperature of 150°C to 500°C is applied to allow the thermal crosslinking reaction to proceed. Crosslinking can improve heat resistance and chemical resistance. This heat treatment method can be selected by selecting a temperature and gradually increasing the temperature, or by selecting a certain temperature range and continuously increasing the temperature for 5 minutes to 5 hours. An example of the former is a method of performing heat treatment at 130°C and 200°C for 30 minutes each. An example of the latter is a method of linearly increasing the temperature from room temperature to 400°C over 2 hours.

[0091] The cured film of the present invention is a cured film obtained by curing the resin composition of the present invention or the resin composition film of the present invention. The cured film of the present invention obtained by curing the resin composition of the present invention or the resin composition film of the present invention can be used for electronic components such as semiconductor devices. The semiconductor device in the present invention refers to devices in general that can function by utilizing the characteristics of semiconductor elements. Electro-optical devices and semiconductor circuit boards in which semiconductor elements are connected to a substrate, stacks of multiple semiconductor elements, and electronic devices containing these are all included in semiconductor devices. In addition, electronic components such as multilayer wiring boards for connecting semiconductor elements are also included in semiconductor devices. Specifically, the film is preferably used for applications such as a passivation film for semiconductors, a surface protection film for semiconductor elements, an interlayer insulating film between semiconductor elements and wiring, an interlayer insulating film between multiple semiconductor elements, an interlayer insulating film between wiring layers of multilayer wiring for high-density mounting, and an insulating layer for organic electroluminescent elements, but is not limited thereto and can be used for various applications.

[0092] The cured film of the present invention can be used as a roof part of a structure having a hollow part (hereinafter referred to as a hollow structure). That is, the hollow structure of the present invention is a hollow structure in which the roof part of the hollow structure is the cured film of the present invention.

[0093] The hollow structure is a structure consisting of a recess or protrusion and a roof portion provided in an electronic component, and is formed by thermocompression bonding the resin composition film of the present invention to the recess or protrusion portion. Thereafter, if necessary, unnecessary portions are removed by the above-mentioned pattern processing method, and the structure is heated to form the roof portion of the hollow structure.

[0094] The thickness of the roof part of the hollow structure of the present invention is preferably 10 μm or more and 30 μm or less. If the thickness of the roof part is 10 μm or more, it is preferable in that the membrane strength of the roof part is improved when the hollow structure is formed. On the other hand, if the thickness of the roof part is 30 μm or less, it is preferable in that the hollow structure can be made thin, which contributes to miniaturization of electronic components.

[0095] Furthermore, the hollow structure having the cured film of the present invention is preferably sealed with a molded resin to enhance the robustness of the electronic component. In other words, the hollow structure of the present invention is preferably a structure in which the outer periphery is sealed with a molded resin. When sealing the outer periphery of the hollow structure with a molded resin, a transfer molding method or a compression molding method is generally used. The above-mentioned molding method is formed by pouring a sealing resin melted at about 180°C around the electronic component at a pressure of about 6 MPa. In other words, during this sealing, a pressure of about 6 MPa at high temperature is applied to the roof part of the hollow structure. If the film strength of the cured film used as the roof part of the hollow structure is low, the roof part of the hollow structure may bend and the structure may collapse. In this respect, the hollow structure using the cured film of the present invention as the roof part of the hollow structure has sufficient film strength, and therefore the yield of electronic components in the sealing process of the molded resin is improved.

[0096] The resin composition film of the present invention preferably has a weight loss rate of 0.01% or more and 1.0% or less when the resin composition coating is heated at 200° C. By having the weight loss rate within the above range, outgassing components from the resin composition coating can be suppressed when a cured film is formed as the roof portion of the hollow structure, and the roof structure can be prevented from expanding excessively or from bending due to cure shrinkage.

[0097] The weight loss rate when heated to 200°C can be calculated by using a thermogravimetric analyzer to weigh out 8 to 12 mg of the resin composition coating, purging with nitrogen gas at 100 mL / min and holding the film at 40°C for 10 minutes as the base weight, and then heating the film from 40°C to 200°C at a heating rate of 10°C / min and holding the film for 60 minutes.

[0098] In addition, the resin composition film of the present invention has a melt viscosity of the resin composition coating at 40° C. of 0.5×10 6 MPa s or more, 1.0×10 7 The resin composition film preferably has a melt viscosity of 0.5×10 MPa·s or less at 40° C. 6 When the melt viscosity of the resin composition film is 1.0×10 or more at 40°C, the tackiness of the film surface at room temperature is reduced, and the film can be easily handled. 7 When the compressive strength is MPa·s or less, cracks in the film at room temperature are reduced, defects in the film are reduced, and the yield is improved.

[0099] The melt viscosity of the resin composition film at 40°C can be measured by the following method. First, the resin composition films are placed facing each other and heat-pressed at 60°C to obtain a laminated resin composition film. The above operation is repeated to laminate the resin composition film to a thickness of 600 to 700 μm. Next, the complex melt viscosity at 40°C can be obtained by reading the value of the complex melt viscosity at 40°C when the laminated resin composition film is used and heated at a frequency of 0.2 Hz, a strain amount of 1.0%, and a heating rate of 2°C / min from 30°C to 80°C using a rheometer.

[0100] As described above, the resin composition of the present invention can be used as the roof part of the inner structure. In particular, when used as the roof part, it is preferable that the creep deformation amount at 180 ° C. after the resin composition coating of the resin composition film is thermally cured is 0.5% or more and 2.5% or less. If the creep deformation amount is 0.5% or more, the toughness of the cured film is high, and when an electronic component having the cured film of the present invention as a roof structure of a hollow structure is sealed with a mold resin, the occurrence of cracks in the roof structure is suppressed, and the yield of the electronic component is improved. On the other hand, if the creep deformation amount is 2.5% or less, when sealed with a mold resin, the deflection of the roof structure due to the pressure during mold sealing is suppressed, and the yield of the mold-sealed electronic component can be improved while maintaining the hollow structure part.

[0101] The measurement method of creep deformation amount at 180 ° C after the resin composition coating is thermally cured can be carried out as follows. First, the resin composition film on which a resin composition coating of 30 μm thickness is formed is thermocompressed to the glossy surface of the copper foil. After that, the base film is peeled off, and then exposure is performed using an exposure machine as necessary. Then, using an inert oven, heat curing is performed at 180 ° C for 1 hour. The obtained copper foil with the cured film is etched using a ferric chloride solution to obtain a cured film of the resin composition coating. Next, the obtained cured film is cut into a size of 8 cm x 1 cm. Then, using a universal testing machine, the obtained cured film sample is set in a chamber at 180 ° C, and held for 6 minutes until the temperature stabilizes, and then a tensile load is applied with a constant load of 5 N with a chuck interval of 5 cm, and the deformation amount after 300 seconds is read, so that the creep deformation amount can be measured. EXAMPLES

[0102] The present invention will be specifically described below based on examples, but the present invention is not limited thereto.

[0103] <Evaluation of pattern processability> The protective film of the resin composition film produced in each Example and Comparative Example was peeled off, and the peeled surface was laminated onto a 4-inch silicon wafer using a vacuum diaphragm laminator (MVLP-500 / 600, manufactured by Meiki Seisakusho Co., Ltd.) under the conditions of upper and lower heat platen temperature of 80°C, vacuuming time of 20 seconds, vacuum press time of 30 seconds, and application pressure of 0.5 MPa, forming a resin composition film on the silicon wafer. Then, after peeling off the support film, a mask having a pattern with via sizes of 30 μmφ, 20 μmφ, and 10 μmφ was set in the exposure device, and an exposure amount of 1000 mJ / cm was applied using an ultra-high pressure mercury lamp under the condition of an exposure gap of 100 μm between the mask and the photosensitive resin composition film. 2 (i-line equivalent, full wavelength exposure). After exposure, post-exposure heating was performed on a hot plate at 120°C for 10 minutes. Thereafter, the unexposed areas were removed using a 2.38 mass% aqueous solution of tetramethylammonium hydroxide by dip development, and the substrate was rinsed with water. The development time was set to twice the time required for the unexposed areas to completely dissolve. The pattern thus obtained was observed under an optical microscope, and the smallest size when there were no abnormalities such as clogging in the pattern was used to evaluate the pattern processability. In addition, a pattern that was completely dissolved was rated as 0 (bad).

[0104] <Evaluation of glass transition temperature> In the same manner as in the evaluation method of the pattern processability, the substrate was changed from a silicon wafer to a copper foil (CF-T9DA-SV-1, manufactured by Fukuda Metal Foil and Powder Co., Ltd.) having a planar size of 10 cm x 10 cm, and a resin composition film was formed on the copper foil. After peeling off the support film, an ultra-high pressure mercury lamp was used to expose the copper foil to an exposure dose of 1000 mJ / cm. 2 (i-line equivalent, full wavelength exposure). After exposure, post-exposure heating was performed on a hot plate at 120°C for 10 minutes. Then, using an inert oven (INL-60, manufactured by Koyo Thermo Systems Co., Ltd.), the temperature was raised from room temperature to 200°C over 60 minutes in an N2 atmosphere (oxygen concentration 20 ppm or less), and then heat treatment was performed at 200°C for 60 minutes to obtain a cured film of the resin composition film formed on the copper foil.

[0105] Thereafter, the resin composition film formed on the copper foil was dissolved only in a ferric chloride solution, washed with water, and air-dried to obtain a cured film of the resin composition film alone. The obtained cured film was cut into a test piece of 5 mm x 40 mm size, and measured using a dynamic viscoelasticity measuring device DVA-200 (manufactured by IT Measurement and Control Co., Ltd.) under the conditions of a chuck distance of 20 mm, a frequency of 1 Hz, a temperature range of room temperature to 350 ° C, a heating rate of 5 ° C / min, and a measurement strain of 0.1%, and the peak top temperature of tan δ = storage elastic modulus / loss elastic modulus, which is the ratio of the storage elastic modulus and the loss elastic modulus, was taken as the glass transition temperature. In addition, although the pattern was dissolved in the above evaluation of pattern processability, the evaluation of the glass transition temperature was not performed and was set to 0 (bad).

[0106] <Evaluation of tensile strength and tensile elongation> A cured film of the resin composition film alone was obtained in the same manner as in the evaluation method of the glass transition temperature. The obtained cured film was cut into a test piece of 10 mm x 80 mm size, and a tensile test was performed at room temperature, with a chuck distance of 50 mm and a tensile speed of 50 mm / min using a universal testing machine AG-Xplus (manufactured by Shimadzu Corporation) and a 50 N load cell, to measure the tensile strength (stress at break) and tensile elongation (elongation at break). Measurements were performed on 10 test pieces per specimen, and the average value of the top 5 points was calculated from the results. In addition, although the pattern was dissolved in the evaluation of the above pattern processability, the evaluation of tensile strength and tensile elongation was not performed and was rated 0 (bad).

[0107] The compounds used in the examples and comparative examples were synthesized by the following methods.

[0108] Synthesis Example 1 Synthesis of hydroxyl group-containing diamine compound (a) 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (hereinafter referred to as BAHF) (18.3 g, 0.05 mol) was dissolved in 100 mL of acetone and propylene oxide (17.4 g, 0.3 mol) and cooled to -15°C. A solution of 3-nitrobenzoyl chloride (20.4 g, 0.11 mol) dissolved in 100 mL of acetone was added dropwise to the solution. After the addition was completed, the mixture was reacted at -15°C for 4 hours and then returned to room temperature. The precipitated white solid was filtered and dried in vacuum at 50°C.

[0109] 30 g of the obtained white solid was placed in a 300 mL stainless steel autoclave and dispersed in 250 mL of methyl cellosolve, and 2 g of 5% palladium-carbon was added. Hydrogen was introduced into the mixture using a balloon, and the reduction reaction was carried out at room temperature. After about 2 hours, the reaction was terminated when it was confirmed that the balloon was no longer deflating. After the reaction was completed, the mixture was filtered to remove the palladium compound catalyst, and the mixture was concentrated using a rotary evaporator to obtain a hydroxyl group-containing diamine compound (a) represented by the following formula. The obtained solid was used in the reaction as is.

[0110] [ka]

[0111] Synthesis Example 2: Synthesis of polyamide (A-1) Under a dry nitrogen stream, BAHF (29.30 g, 0.08 mol) was added to 100 g of γ-butyrolactone (hereinafter referred to as GBL) and dissolved by stirring at room temperature. Then, while maintaining the temperature of the reaction solution at -10 to 0°C, 4,4'-diphenyletherdicarboxylic acid dichloride (29.52, 0.1 mol) was added little by little, and after the addition was completed, the temperature was raised to room temperature and stirring was continued for 3 hours. Next, the reaction solution was poured into 3 L of water to collect a white precipitate. This precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 5 hours.

[0112] Synthesis Example 3: Synthesis of polyimide (A-2) Under a dry nitrogen stream, BAHF (29.30 g, 0.08 mol) was added to 80 g of GBL and dissolved by stirring at 120°C. Next, 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride (hereinafter referred to as TDA-100) (30.03 g, 0.1 mol) was added together with 20 g of GBL and stirred at 120°C for 1 hour, and then at 200°C for 4 hours to obtain a reaction solution. Next, the reaction solution was poured into 3 L of water to collect a white precipitate. This precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 5 hours.

[0113] Synthesis Example 4 Synthesis of polyamideimide (A-3) Hydroxyl-containing diamine compound (a) (31.43 g, 0.08 mol) was added to 80 g of GBL under a dry nitrogen stream and stirred at 120°C. Next, TDA-100 (30.03 g, 0.1 mol) was added together with 20 g of GBL and stirred at 120°C for 1 hour, then at 200°C for 4 hours to obtain a reaction solution. Next, the reaction solution was poured into 3 L of water to collect a white precipitate. This precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 5 hours.

[0114] Synthesis Example 5 Synthesis of polyimide (A-4) Under a dry nitrogen stream, BAHF (25.64 g, 0.07 mol) was added to 70 g of GBL and dissolved by stirring at 120°C. Next, norbornane-2-spiro-2'-cyclopentanone-5'-spiro-2''-norbornane-5,5'',6,6''-tetracarboxylic dianhydride (38.44 g, 0.1 mol) was added together with 20 g of GBL and stirred at 120°C for 1 hour, and then at 200°C for 4 hours to obtain a reaction solution. Next, the reaction solution was poured into 3 L of water to collect a white precipitate. This precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 5 hours.

[0115] Example 1 10 g of polyamide (A-1) obtained in Synthesis Example 2 as component (A), 10 g of TEPIC-VL (trade name, manufactured by Nissan Chemical Industries, Ltd.) as component (B), 0.6 g of CPI-310B (trade name, manufactured by San-Apro Co., Ltd.) as component (C), and 0.8 g of KBM-403 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.) as a silane compound were dissolved in GBL. The amount of solvent added was adjusted so that the solid content concentration was 60% by weight, with additives other than the solvent being considered as solid content. Thereafter, pressure filtration was performed using a filter with a retention particle size of 1 μm to obtain a resin composition varnish.

[0116] The obtained resin composition varnish was applied onto a 50 μm thick PET film using a comma roll coater, and dried at 120 ° C for 8 minutes, and then a 10 μm thick PP film was laminated as a protective film to obtain a resin composition film. The thickness of the resin composition film was adjusted to 25 μm. The obtained resin composition film was used to evaluate the pattern processability, glass transition temperature, tensile strength, and tensile elongation as described above. The results are shown in Table 1.

[0117] Examples 2 to 9 Resin composition films were prepared in the same manner as in Example 1, except that the components (A) to (C) and other components were changed to compounds having the structures shown below and their mixing ratios were changed as shown in Table 1. The pattern processability, glass transition temperature, tensile strength, and tensile elongation were evaluated as described above. The results are shown in Table 1.

[0118] Example 10 A resin composition film was prepared in the same manner as in Example 2, and the pattern processability was evaluated in the same manner as described above, except that the 2.38 mass% aqueous solution of tetramethylammonium hydroxide was changed to propylene glycol monomethyl ether acetate, and the rinsing water was changed to isopropyl alcohol. The results are shown in Table 1.

[0119] Comparative Example 1 Resin composition films were prepared in the same manner as in Example 9, except that the components (A) to (C) and other components were changed to compounds having the structures shown below and their mixing ratios were changed as shown in Table 1. The pattern processability, glass transition temperature, tensile strength, and tensile elongation were evaluated as described above. The results are shown in Table 1.

[0120] [Table 1]

[0121] [Table 2]

[0122] The structures of the compounds used in each of the Synthesis Examples, Examples and Comparative Examples are shown below.

[0123] (A) Polymer compound A-1: Polyamide with carboxylic acid residues at the molecular chain end A-2: Polyimide with carboxylic acid residues at the molecular chain terminals A-3: Polyamideimide with carboxylic acid residues at the molecular chain terminals A-4: Polyimide with carboxylic acid residues at the molecular chain terminals.

[0124] Polymers other than (A) 1007 (BisA type phenoxy resin, manufactured by Mitsubishi Chemical Corporation) (B) Cationic polymerizable compound TEPIC-VL (Nissan Chemical Co., Ltd.), liquid at room temperature, epoxy equivalent = 128g / eq. PETG (Showa Denko K.K.), liquid at room temperature, epoxy equivalent = 90g / eq. BATG (Showa Denko K.K.), liquid at room temperature, epoxy equivalent = 113g / eq.

[0125] [ka]

[0126] (C) Cationic polymerization initiator CPI-210S (sulfonium salt photoacid generator, San-Apro Co., Ltd.) CPI-310B (sulfonium salt photoacid generator, San-Apro Co., Ltd.) Silane Compounds KBM-403 (3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.).

[0127] <Evaluation of weight loss rate> The protective film of the resin composition film produced in each Example and Comparative Example was peeled off, and 8 to 12 mg of the resin composition film was taken out using a spatula. Then, using a thermogravimetric analyzer TG / DTA6200 (manufactured by Hitachi High-Tech Science Co., Ltd.), the temperature was raised from 40°C to 200°C at a heating rate of 10°C / min, and the mass after 60 minutes of holding was read using the weight after 10 minutes of holding at 40°C in a state of purging with nitrogen gas at 100mL / min as a reference, and the weight loss rate was calculated.

[0128] <Melt viscosity> The protective film of the resin composition film prepared in each Example and Comparative Example is peeled off, the resin composition films of the resin composition films are placed opposite each other, and are thermally bonded at 60°C to obtain a laminated resin composition film (a laminate of resin composition films). Next, the laminate of the resin composition film from which the PET film has been peeled off and the resin composition film from which the protective film has been peeled off are placed opposite each other, and are thermally bonded as described above to obtain a laminate of the resin composition film. Thereafter, the above operation is repeated to laminate the resin composition film to a thickness of 600 to 700 μm. Next, the laminate of the resin composition film is used to measure the complex melt viscosity at 40°C using a disposable parallel plate having a diameter of 15 mm, at a frequency of 0.2 Hz, a strain amount of 1.0%, and a temperature rise rate of 2°C / min from 30°C to 80°C.

[0129] <Creep deformation amount> A cured film of the resin composition film alone was obtained in the same manner as in the evaluation method of the glass transition temperature, except that the thickness of the resin composition coating was 30 μm. The obtained cured film was cut into a test piece of 10 mm × 80 mm size, and set in a chamber at 180 ° C. using a universal testing machine AG-Xplus (manufactured by Shimadzu Corporation) and a 50 N load cell, and held for 6 minutes until the temperature stabilized, and then a tensile load of 5 N was applied with a chuck interval of 5 cm, and the deformation amount after 300 seconds was read, and the deformation amount from the initial chuck interval was taken as the creep deformation amount.

[0130] Examples 11-12 The resin composition films of Examples 2 and 5 were used to evaluate the weight loss rate, melt viscosity, and creep deformation amount as described above. The results are shown in Table 2.

[0131] Comparative Example 2 The weight loss rate, melt viscosity, and creep deformation amount were evaluated as described above using the resin composition film of Comparative Example 1. The results are shown in Table 1.

Claims

1. A negative-type photosensitive resin composition that contains (A) a polymer compound and (B) a cationic polymerizable compound and is cured by a cationic polymerization reaction, The polymer compound (A) is at least one compound selected from the group consisting of polyimide and polyamideimide, the polymer compound (A) has a structure derived from an alicyclic tetracarboxylic acid dianhydride, the (A) polymer compound has a structure in which a molecular chain terminal is derived from a carboxylic acid residue, The resin composition further comprises (C) a cationic polymerization initiator.

2. 2. The negative type photosensitive resin composition according to claim 1, wherein the polymer compound (A) has a structure derived from a compound represented by at least one of the following general formulas (3) and (4): 【Chemistry 1】 (In the formula, R 1 , R 2 , R 3 each independently represents a hydrogen atom or a methyl group.

3. 3. The negative type photosensitive resin composition according to claim 1, wherein the content of the cationically polymerizable compound (B) relative to 100 parts by mass of the polymer compound (A) is 50 to 150 parts by mass.

4. A negative type photosensitive resin composition film having a resin composition coating formed from the negative type photosensitive resin composition according to any one of claims 1 to 3.

5. A cured film obtained by curing a resin composition coating of the negative type photosensitive resin composition according to any one of claims 1 to 3 or the negative type photosensitive resin composition film according to claim 4.

6. An electronic component comprising the cured film according to claim 5 .

Citation Information

Patent Citations

  • Negative photosensitive resin composition and cured object thereof

    JP2005250161A

  • Photosensitive resin composition and electronic apparatus

    JP2019038964A

  • Photosensitive resin composition, layered product thereof, cured object therefrom, and method of forming pattern from the composition (3)

    WO2008007764A1

  • Resin and photosensitive resin composition

    WO2016035593A1

  • Photosensitive resin composition, method for manufacturing cured resin film, and semiconductor device

    WO2016140024A1